Consider the impact of small decisions on your campus safety office. Issue 10 (9th January 2020) - Skipworth, Stan
Abstract : Decision‐making, even when difficult, is essential to the role of effective campus safety leadership. And while you can know ahead of time that some of these choices possess significantly greater implications, often with the added tension of time constraints, other decisions may not seem to carry the same weight in the day‐to‐day progress of our teams. I've personally opted for one solution over another, only to realize that time amplified the effects of my decision for my office.